Impact of emotionality and locus of control on athletes` motivation for success achievement and failure avoidance in individual sports - Popovych, I.; Bokhonkova, Y.; Sokolova, H.; Forostian, O.; Rodchenkova, I.; Yurkiv, Y.; Korniienko, I. (Journal of Physical Education and Sport, 2024)
This study aimed to identify statistically significant parameters regarding the influence of emotionality and locus of control on athletes' motivation for success achievement and failure avoidance in individual sports. The sample consisted of athletes participating in individual sports (n = 123) with a mean age of 23 (Me = 23; M = 23.19; SD = ±2.92), representing disciplines such as artistic gymnastics, track and field, weightlifting, freestyle wrestling, and boxing. Among the participants were medalists and winners of regional, national, international, and Olympic sports competitions. Methods. The methods verified in sports studies allowed measuring a number of parameters of emotionality and locus-control, and also two dependent variables - motivation for achieving success and avoiding failure. Statistically significant differences were identified by standard coefficients. Results. It was empirically established that both dependent variables have a considerable number of statistically significant correlations (p = .050; p = .010): motivation for achieving success has eight correlations, motivation for avoiding failure has seven correlations. It was found that three parameters - "athletes` emotional stability", "area of athletes` achievements" and "athletes` health and illnesses" correlate significantly with both motivations: motivation for achieving success (MAS) and motivation for avoiding failure (MAF). Diametrically opposite correlations of the parameters "athletes` interpersonal relationships" with MAS (rxy = -.235; p=.041) and MAF (rxy = .215; p = .045) and "athletes` sporting activities" with MAS (rxy = .623; p = .041) and MAF (rxy = -.238; p=.042) were established. Discussion and conclusions. It was generalized that emotional stability (ES) and emotional arousal (EA) are important parameters of athletes` emotionality, whose constructive realization is within the scope of emotional intelligence (EQ) and has a statistically significant impact on motivation and achievement of victory. It was explained that support for emotional positive relationships in domination of motivation for achieving success can have a negative effect on athletes` concentration. Such relationships can be a defense mechanism, emotional comfort and psychological relief in difficult situations of sporting activities in case of domination of motivation for avoiding failure. It was proved that emotionality and locus-control affect motivation for achieving success and avoiding failure of athletes in individual sports. The obtained results are characterized by scientific novelty and can arouse interest in everyone who is involved in training and competition processes of athletes in individual sports.